Abstracts of the International Halal Science Conference 2023 (IHASC23) - Hazahari, Noor Yuslida (AIJR Publisher, 2023)
This book presents the extended abstracts of the selected contributions to the International Halal Science Conference, held on 22-23 August 2023 by the International Institute for Halal Research and Training (INHART), IIUM, Malaysia in collaboration with Halalan Thayyiban Research Centre, University Islam Sultan Sharif (UNISSA), Brunei Darussalam. With the increasing global interest in halal products and services, this conference is timely.